Associations between genomic copy number alterations and clinical and laboratory results in pediatric B-cell acute lymphoblastic leukemia - Aisyi, Mururul; Andriastuti, Murti; Kosasih, Agus Susanto; Utomo, Ahmad Rusdan Handoyo; Saputra, Fahreza; Sari, Teny Tjitra; Sjakti, Hikari Ambara; Dwijayanti, Fifi; Harimurti, Kuntjoro (Paediatrica Indonesiana, 2025)
Background Copy Number Alterations (CNAs) are changes in DNA structure that lead to gain or loss of copies of DNA sections in the genome. They correlate with unfavorable prognostic outcomes in pediatric leukemia, influencing treatment resistance, relapse rates, and overall survival. Identifying high-risk patients with a likelihood of CNA positivity is essential for understanding its association with clinical characteristics and laboratory findings. Since routine CNA testing is costly, recognizing simple clinical and laboratory markers that predict CNA presence can help focus screening efforts, enabling more efficient risk stratification and prognosis assessment in acute leukemia Objective To describe the characteristics and analyze for associations between CNA, clinical characteristics, and laboratory findings in pediatric ALL patients. Methods This cross-sectional observational study included B-cell acute lymphoblastic leukemia (ALL) patients from three hospitals, excluding those above 18 years. Data collected encompassed demographics, clinical features, and laboratory results. We performed multiplex ligation-dependent probe amplification (MLPA) testing to identify CNA positivity. Results From January to December 2019, there were 74 pediatric ALL patients incuded in our study; 26 of them had positive results and the remaining 48 had negative results. CNA-positive status was commonly found in subjects aged ? 5 years (38.6%), while CNA-negative status was highest in patients aged ? 10 years (72.7%). CNA-positive status was significantly higher in patients with lymphadenopathy, lower hemoglobin level (7.73 g/dL), and lower platelet level (52,019/µL) (P<0.05). Conclusion Patients with lymphadenopathy, lower hemoglobin, and lower platelet levels are more likely to test positive for CNA. However, more research is needed to fully understand the implications of this finding and its potential impact on patient care.